Navigating Sustainability In the Tourism and Hospitality Industry: Transformation Under the Influence of Climatic Challenges - Mohammad Abul Basher Rasel (SocioEconomic Challenges)
This study investigates how sustainability practices are shaping the tourism and hospitality industry by examining practitioners' ̂motivations, impacts, as well as challenges that will be encountered. Identifying practical motivators of sustainable behavior in firms through semi-structured interviews with 15 professionals (managers, sustainability officers and frequent guests), this study enlists important drivers like alignment with brand strategy, as well as the cost efficiency of eco-friendly practices, placing the employees and firms on a path to sustainability. Sustainability measures have been shown to improve operational efficiency, with energy conservation technologies leading to utility cost savings of up to 25% and waste management practices producing cost reductions of 10%. Additionally, sustainability efforts like local sourcing played a role in customer satisfaction with 70% of guests indicating that they were more likely to enjoy businesses which supported local communities. While there were some advantages to adoption, such as cost savings and greater productivity, practitioners noted barriers including high upfront costs and ongoing employee training, a particular problem in smaller enterprises with high turnover. The key contributions of the research lie in focusing on valuable short-term financial or reputational benefits of sustainability practices and identifying operational pitfalls that can act as barriers to effective implementation. These indicate, in turn, the imperative of continuous support of industry whether through subsidies or incentives to be able to transit sustainably within the tourism and hospitality sectors.